-2r-3=6r+4

Simple and best practice solution for -2r-3=6r+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2r-3=6r+4 equation:


Simplifying
-2r + -3 = 6r + 4

Reorder the terms:
-3 + -2r = 6r + 4

Reorder the terms:
-3 + -2r = 4 + 6r

Solving
-3 + -2r = 4 + 6r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-6r' to each side of the equation.
-3 + -2r + -6r = 4 + 6r + -6r

Combine like terms: -2r + -6r = -8r
-3 + -8r = 4 + 6r + -6r

Combine like terms: 6r + -6r = 0
-3 + -8r = 4 + 0
-3 + -8r = 4

Add '3' to each side of the equation.
-3 + 3 + -8r = 4 + 3

Combine like terms: -3 + 3 = 0
0 + -8r = 4 + 3
-8r = 4 + 3

Combine like terms: 4 + 3 = 7
-8r = 7

Divide each side by '-8'.
r = -0.875

Simplifying
r = -0.875

See similar equations:

| n^2-2n-1=38.5 | | (x/11)=(x/12)-14 | | n^2-2n-2=38.5 | | 6g-4(-6+3g)=1-g | | -5p+6+6p=11 | | -3/5-3/10 | | 8.4x+16.28=-11.6+16.04 | | 3-/5-3/10 | | x^2+8x+8=3x+4 | | 24+16x=75+17x | | (2z-3)(z+4)=(3z-2)(z+6) | | (-5p+8)=(7p-5) | | 4x+2=3(x-3)+5 | | 0=-5t+15 | | 7.6x-1.1=29.3 | | 2[3-(-8x-8)]=80x+86 | | 1.7+x=7.1 | | 2+1x=1 | | 2l+2(70)=600 | | 4/5x-8=9/5x | | -2y-16=0 | | x^2-9x-14=-6x+4 | | 3/4*.1=8 | | 3(6z-1)-4(z+2)=6(z+1) | | x^2-2x-27=8 | | 2(56-13)= | | -1=b^4-7 | | Abs(x-2)=22 | | 1.92-0.33= | | 3-2/2--4 | | -8u=24 | | -15-2x=16-1(3x-9) |

Equations solver categories